THE ADJECTIVE AND ITS TYPES IN THE BOOK “WASHÔYÂ AL-ABÂ LIL ABNÂ” BY MUHAMMAD SHAKER AL-ISKANDARI: A GRAMMATICAL ANALYTICAL STUDY - Budiman, Agus; Nabila, Wardah Hani; Ismail, Mohammad; Sakinah, Khoirus; Muttaqin, Rokhmat (Abjadia : International Journal of Education, 2024)
The study of Nahwu, a branch of Arabic grammar, focuses on changes in word endings related to i'rab (inflection) and bina (construction), as well as sentence structure. Within Nahwu, the concept of tawabi’ refers to words that follow another in agreement with case, definiteness, and other grammatical aspects. Tawabi’ is categorized into na’at (adjective), taukid (emphasis), badal (substitute), and athaf (conjunction). This research specifically analyzes na’at and its types in the book "Washôyâ Al-abâ Lil Abnâ" by Muhammad Syakir Al-Iskandarî, which is widely used in Islamic educational institutions. The objectives are to identify and categorize the types of na’at in the text. Using a literature research method, the study employs documentation and data analysis based on the Miles and Huberman theory, involving data restriction, grouping, and presentation. The findings reveal 97 instances of na’at in the book, with 96 being na’at haqiqi (direct adjectives) and 1 being na’at sababi (causal adjective). The types of na’at identified include mufrod (single words), jumlah (sentences, both nominal and verbal), and syibhul jumlah (prepositional phrases), with the majority being na’at haqiqi mufrod. The study suggests further research to deepen the exploration of tawabi’, particularly na’at.